New poly(ionic liquid)s based on poly(azomethine-pyridinium) salts and its use as heterogeneous catalysts for CO2 conversion. (January 2019) - Maya, Eva M.; Verde-Sesto, Ester; Mantione, Daniele; Iglesias, Marta; Mecerreyes, David
Graphical abstract: Highlights: New poly(azomethine pyridinium) salts synthesized under microwave irradiation. New family of poly(ionic liquid)s contining pyridinium cations and thermally stable backbones. Hetereogeneous catalysts for the cycloaddition of CO2 to epychlorohydrin. Abstract: A fast and simple synthetic route towards a new family of poly(ionic liquids) based on aromatic crosslinked poly(azomethine-pyridinium) salts is described. These new polymers were prepared in one step from new diamine methyl pyridinium salts and isopthaldehyde, in 30 min under microwave irradiation. By this method, poly(azomethine-pyridinium) containing chloride (Cl), bis(trifluoromethylsulfonyl)imide (TFSI) and hexaflorophosphate (PF6 ) as counter-anions were synthetized. This new pyridinium poly(ionic liquid)s were obtained as insoluble powders showing high thermal stability. The poly(azomethine-pyridinium)s were tested as heterogeneous catalysts in the cycloaddition of CO2 to epichlorohydrin to obtain chloropropylene carbonate. The polymers containing chloride anion shows high content of catalytically active sites and the best performance of the series, with 100% selectivity towards the chloropropylene carbonate in a reaction without solvent at 3 bar of CO2, 100 °C and low catalyst loading (0.5 mol%).